2023
DOI: 10.1002/mnfr.202200308
|View full text |Cite
|
Sign up to set email alerts
|

Proteoforms of β‐Casein, α‐s1‐Casein, α‐Lactalbumin, Serum Albumin, and Lactotransferrin Identified in Different Lactation Phases of Human Milk by Proteomics Approach

Abstract: Scope Human milk (HM) has a wide range of proteins with biological and nutritional functions, essential for newborns. The roles of proteins and their proteoforms in HM are not fully understood. This study aims to assess, by 2‐DE proteomics, the differential proteoforms in HM, present in colostrum (COL), transition (TRA), and mature milk (MAT), aiming to contribute to understanding neonates’ protein needs. Methods and results HM samples are collected from 39 healthy lactating women. COL presents the higher conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We speculated that the upregulation of LALBA was not the direct effect of melatonin but the physiological compensatory effect of the low level of lactose, which was caused by the insufficient galactose transportation into the Golgi apparatus due to the downregulation of SLC35B1. In lactose synthesis, LALBA expression is more easily regulated by multiple factors such as insulin, while BAG4LT is usually unchanged ( Ribeiro et al, 2023 ), which is similar to our results. Therefore, in the current study, we have identified the signal transduction pathway of melatonin in lactose synthesis, i.e., melatonin/MT1/PRLR/SLC35B1/lactose.…”
Section: Discussionsupporting
confidence: 91%
“…We speculated that the upregulation of LALBA was not the direct effect of melatonin but the physiological compensatory effect of the low level of lactose, which was caused by the insufficient galactose transportation into the Golgi apparatus due to the downregulation of SLC35B1. In lactose synthesis, LALBA expression is more easily regulated by multiple factors such as insulin, while BAG4LT is usually unchanged ( Ribeiro et al, 2023 ), which is similar to our results. Therefore, in the current study, we have identified the signal transduction pathway of melatonin in lactose synthesis, i.e., melatonin/MT1/PRLR/SLC35B1/lactose.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, mature human milk primarily contains caseins, such as CSN2 and CSN1S1, which are crucial for metabolic processes that increase muscle mass, boost the immune system, and generate energy. 95 There have also been some studies on the changes in human whey and MFGM proteins following post-translational modifications during lactation. Label-free glycoproteomics was used to identify 2617 and 986 unique site-specific N-glycans from 221 and 200 MFGM glycoproteins in DC and donkey mature milk (DM), respectively.…”
Section: Advances In Human Milkmentioning
confidence: 99%
“…Human colostrum contains proteins related to the immune system such as lactotransferrin (LTF) and immunoglobulins (Igs). In contrast, mature human milk primarily contains caseins, such as CSN2 and CSN1S1, which are crucial for metabolic processes that increase muscle mass, boost the immune system, and generate energy . There have also been some studies on the changes in human whey and MFGM proteins following post-translational modifications during lactation.…”
Section: Proteome-based Investigation Of the Effects Of Protein Analy...mentioning
confidence: 99%